Distribusi Hasil Tangkapan Gurita di Desa Kalupapi Kecamatan BangkurungKabupaten Banggai Laut | Distribution of Octopus Catches in Kalupapi Village, Bangkurung District, Banggai Laut Regency - Nurfadila Matta; Aziz Salam; Nuralim Pasisingi (The NIKe Journal, 2026)
This research aims to understand the distribution channels of octopus catches, catch results, fishermen's profits, and marketing margins of octopus (Octopus spp.) in Kalupapi Village, Bangkurung District, Banggai Laut Regency. Sampling was conducted from June to July 2024. This study uses a descriptive analysis of octopus catch distribution patterns. Primary data was obtained through interviews with respondents Meanwhile, secondary data consisted of document data gathered from the research location. The research results indicate that the distribution of octopus catches in Kalupapi Village, Bangkurung District, Banggai Laut Regency, is carried out through a trade channel, specifically from fishermen to collectors, from collectors to wholesalers, from wholesalers to agents, and finally from agents to the food processing industry. The average monthly income for octopus fishermen in Kalupapi Village, Bangkurung District, Banggai Laut Regency, is Rp 2,325,205. The average monthly profit for octopus fishermen in Kalupapi Village is Rp 1,587,534, and the octopus marketing margin is Rp 10,000/kg.